Decompensated Acute Heart Failure Accompanied with Cardiac Cirrhosis and Chronic Disease Anemia in Child - Tommy Darmasaputra (Archives of The Medicine and Case Reports, 2020)
Continuous heart failure can lead to complications to other systems, one of which is the hepatic system. Heart failure results in venous congestion in the portal vein so that the portal vein pressure increases, which is called portal hypertension. Portal hypertension causes fluid to pass through the walls of blood vessels and into the tissues. Management of decompensatory heart failure accompanied by comorbi d disease in cardiac cirrhosis includes drugs management that does not aggravate the liver, namely angiotensin converting enzyme inhibitors and loop diuretic agents. Also, non-pharmacological management such as resting position and a diet sufficient in protein and low salt help improve the patient's general condition. This case report aims to present a de compensated heart failure accompanied by cardiac cirrhosis and anaemia of chronic disease in a child.